TRENDS IN EARLY CHILDHOOD DEVELOPMENT: A BIBLIOMETRIC STUDY AND RESEARCH AGENDA - JENIFFER XIMENA VEGA FAJARDO , ANDREA DEL PILAR BERNAL LÓPEZ , PAULA ANDREA SAAVEDRA PARRA SONIA LUCÍA VARGAS AMÉZQUITA , ERIKA YAMILA MELO ROMERO (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Child development is a fundamental field of study that encompasses interrelated dimensions such as physical, cognitive, emotional, social, and spiritual growth. The aim of this study was to analyze research trends on child development between 2020 and 2025, with emphasis on the cognitive, affective, social, physical, and spiritual dimensions. A bibliometric and scientific mapping approach was used, with Scopus as the primary data source. Specific keyword-based search criteria were applied, and tools such as VOSviewer were used to identify patterns of co-occurrence, co-citation, and scientific production networks. A total of 16,013 articles were analyzed after filtering by language, document type, and publication period. The results revealed a progressive decline in scientific output related to child development, particularly in the spiritual dimension, which showed significantly lower representation compared to the others. Thematic analysis identified relevant clusters in each dimension, as well as authors and countries with the highest scientific connectivity. This study not only highlights prevailing lines of research but also proposes an agenda for future exploration, with special emphasis on interdisciplinary and underrepresented areas such as spiritual development. Overall, the study provides an updated and relevant perspective to guide new research and public policies focused on early childhood.